A policy paper on the socio-economics of the Visayas Sea fisheries sector focus on marketing and credit - Hernando, Christine Mae D (Iloilo City U.P. in the Visayas, College of Management, 2005)
The study reviews currnt policy and legal framework for fisheries marketing and credit; describes existing market and credit arrangements for economic activities of small, subsistence fisher folks and commercial fishermen and their implications on enterprise development and resource management; and, recommends appropriate policies and other measures to improve markets and access to credit for the fisheries sector in the Visayan sea Area. The review and analysis of current fishery policies and legislation reveal significant effort of policy makers to improve on P.D. No. 704, the previous national fishery law, which focused on maximizing fishery production and development. RA 8550 as the current national fishery law signifies an important pardigm shift from a purely economic conception of resource use to one of responsible stewardship for purposes of sustainability.Still cognizant of the need to support and develop the fishery industry especially municipal fisheries, the Fisheries Code provides for the establishment of the necessary post harvest infrastructure and facilities such as fish ports, cold storage, and processing centers. Policy outcomes are seen in increased production of fishery resources as stated in reports and documentation, but their impact on fishery stakeholders especially the subsistence fishermen has yet to determined and documented. Policy feedback shows a negative public perception of the working of current fishery policy. Feedback from the more informed sectors reveal that current policy efforts leave much to be desired in terms of prohibition with corresponding sanctions on the use of municipal waters by commercial fishers. The study recommends Strengthening Cooperative Fishery Enterprises as one policy initiative to address marketing and credit needs of small fishers in the Visayan Sea. Its important components are 1) cooperative organization and management; 2) establishment of cooperative business services; and 3) cooperative networking and linkaging. Another policy recommended is on Community Governance. It is intended to support cooperative strengthening efforts through enhanced local government capabilities in the areas of strategic linkaging with other sectors, implementation of fishery laws and CBCRM in coordination with local fishery cooperatives, and improving local fiscal management capabilities. The study also recommends poverty mapping, participatory action resarch, and assessment of training needs and opportunities to provide database for the formulation of pverty alleviation measures and development interventions especially in the design of alternative livelihood enterprise.
Research Paper -- Iloilo City : U.P. in the Visayas, [2005].
Keywords: Visayan Sea fisheries sector -- Economic condition